Testosterone and Cholesterol Vasodilation of Rat Aorta Involves L-Type Calcium Channel Inhibition - E. Álvarez; E. Cairrão; M. Morgado; C. Morais; I. Verde (Hindawi Limited, 2010)
Testosterone has rapid nongenomic vasodilator effects which could be involved in protective cardiovascular actions. Several authors suggested specific mechanisms to explain this effect, but this matter was not clarified yet. We studied the actions of testosterone and cholesterol on endothelium-denuded rat aorta and their effects on the L-type Ca2+ current (ICa,L) and potassium current (IK). Testosterone (1-100 μM) totally relaxed, in a rapid and concentration-dependent way, the aortic rings contracted by KCl or by (−)-Bay K8644 (BAY). Cholesterol also fully relaxed the contractions induced by KCl. None of the potassium channel antagonists tested (glibenclamide, tetraethylammonium and 4-aminopyridine) modified significantly the relaxant effect of testosterone. The antagonist of classic testosterone receptors, flutamide, did not modify the vasorelaxant effect of testosterone. Furthermore, testosterone and cholesterol inhibited either basal and BAY-stimulated ICa,L in A7r5 cells and they have no effects on IK. In summary, our results demonstrate that cholesterol and testosterone relax rat aorta by inhibiting LTCC. This effect of testosterone is not mediated by the classic hormone receptor or by potassium channel activation. These results suggest that the vasodilator mechanism of cholesterol and testosterone is the same.